2006
DOI: 10.1016/s0022-5347(05)00054-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Mass Index on Survival of Patients With Surgically Treated Renal Cell Carcinoma

Abstract: Although an increased BMI was associated with a greater proportion of clear cell histology, comorbidity, and surgical morbidity, BMI did not adversely impact overall or progression-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
52
3
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 13 publications
4
52
3
4
Order By: Relevance
“…One of the significant findings of our study was that obesity was independently associated with better survival or lower risk of tumor recurrence in Korean patients with RCC and venous tumor thrombus. There has been a controversy about a prognostic impact of BMI on survival of patients with RCC (17)(18)(19). Recently, we demonstrated that overweight or obese Korean patients with RCC have more favorable pathological features and a better prognosis than those with normal BMI, which is in accordance with the result from a study by Awakura et al evaluating Japanese patients with RCC (20,21).…”
Section: Discussionsupporting
confidence: 89%
“…One of the significant findings of our study was that obesity was independently associated with better survival or lower risk of tumor recurrence in Korean patients with RCC and venous tumor thrombus. There has been a controversy about a prognostic impact of BMI on survival of patients with RCC (17)(18)(19). Recently, we demonstrated that overweight or obese Korean patients with RCC have more favorable pathological features and a better prognosis than those with normal BMI, which is in accordance with the result from a study by Awakura et al evaluating Japanese patients with RCC (20,21).…”
Section: Discussionsupporting
confidence: 89%
“…We found that statin recipients were more likely to have any history of smoking and a higher BMI, as observed by others. [9][10][11] While several studies have shown that both of these factors are significantly associated with survival in kidney cancer, 7,8,[23][24][25] other studies found no such association; [26][27][28] however, many of those studies showing a significant association for obesity with survival did not control for smoking, [23][24][25] and studies demonstrating an association for smoking with survival did not control for obesity. 29,30 Therefore, the independent prognostic importance of smoking and obesity remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the incidence of both RCC [18] and extreme obesity [9] are increasing, urologists will increasingly have to consider the potential benefits of treatment vs the higher risk of surgical and anaesthetic complications in very obese patients [19]. Recent studies have suggested that obesity increases the risk of developing RCC [1], although mild or moderate obesity is not necessarily associated with worse outcomes [4][5][6][7][19][20][21][22]. In the present study, we evaluated the largest series to date of RCC patients with extreme obesity, and found similar CSS and recurrence rates when compared with patients with lower body mass.…”
Section: Discussionmentioning
confidence: 99%